2002
DOI: 10.1084/jem.20020609
|View full text |Cite
|
Sign up to set email alerts
|

HLA-E–dependent Presentation of Mtb-derived Antigen to Human CD8+ T Cells

Abstract: Previous studies in mice and humans have suggested an important role for CD8+ T cells in host defense to Mtb. Recently, we have described human, Mtb-specific CD8+ cells that are neither HLA-A, B, or C nor group 1 CD1 restricted, and have found that these cells comprise the dominant CD8+ T cell response in latently infected individuals. In this report, three independent methods are used to demonstrate the ability of these cells to recognize Mtb-derived antigen in the context of the monomorphic HLA-E molecule. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
203
3
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 186 publications
(213 citation statements)
references
References 38 publications
4
203
3
3
Order By: Relevance
“…3). Even though the possibility that the anti-HLA-E mAbs used in our studies were weak blockers cannot be ruled out, our results are supported by those reported by Heinzel et al (18), who, in unpublished data, found that mAb to pan-HLA I (clone W6/32) were capable of inhibiting CD8 ϩ T cell-dependent recognition in an HLA-E-restricted system. Unfortunately, the frequencies of effectors that release granzyme B to S. Typhi-infected autologous blasts or S. Typhi-infected 721.221.AEH cannot be directly compared because of the differential expression of HLA-E between these cells (i.e., 721.221.AEH cells express considerably higher numbers of HLA-E molecules than blasts; Fig.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…3). Even though the possibility that the anti-HLA-E mAbs used in our studies were weak blockers cannot be ruled out, our results are supported by those reported by Heinzel et al (18), who, in unpublished data, found that mAb to pan-HLA I (clone W6/32) were capable of inhibiting CD8 ϩ T cell-dependent recognition in an HLA-E-restricted system. Unfortunately, the frequencies of effectors that release granzyme B to S. Typhi-infected autologous blasts or S. Typhi-infected 721.221.AEH cannot be directly compared because of the differential expression of HLA-E between these cells (i.e., 721.221.AEH cells express considerably higher numbers of HLA-E molecules than blasts; Fig.…”
Section: Discussionsupporting
confidence: 82%
“…The HLA class I-defective B cell line 721.221 as well its transfectants 721.221.AEH (which has been transfected with HLA-E fused to the HLA-A2 leader peptide, and therefore express the HLA-E*0101 allele on the cell surface), 721.221.F (which was transfected only with HLA-F), and 721.221.E6 (which was transfected with HLA-E without a leader peptide) were provided by Dr. D. Geraghty (14,18). The 721.221 cell line is characterized by the lack of expression of HLA-class Ia A, B, and C due to gamma ray-induced mutation in the HLA complex.…”
Section: Target/stimulator Cellsmentioning
confidence: 99%
See 3 more Smart Citations